Pattern recognition with Quantum Support Vector Machine(QSVM) on near term quantum processors. - Ahmed, Sajjad (BRAC University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2019.